Methodological tool for calculating the cost-benefit in occupational safety and health (Original) (REDEL. Revista Granmense de Desarrollo Local, 2019)
Implementing a health and safety policy at work is an obligation of companies, not only because there is regulation in this regard, but also because it seeks to protect and improve the physical, mental, social and spiritual health of workers in their jobs. It is also an alternative because prevention has a positive impact on the performance of workers, avoiding additional costs due to an accident at work. Many companies argue that they are very expensive accident prevention activities because they do not see the utility. Therefore, they spare this investment until a serious accident occurs. They do not realize that the effective implementation of these policies ensures a production without paralyzes, with lower costs and an adequate work environment. It is essential that economic analyzes be made based on the close link between the cost and benefit present in this activity, which will allow defending the investments and expenses that must be made to eradicate or reduce risks. The proposed procedure can be used as a tool to measure the cost-benefit of accidents, incidents and common illness, allowing the entity to know how much money is lost by not investing in preventive measures against the identified risks.
Keywords: cost-benefit; prevention; workers